The Psychosocial Impact of Neurobehavioral Disability - Williams, Claire; Wood, Rodger Llewellyn; Alderman, Nick; Worthington, Andrew (Frontiers in Neurology, 2020)
Neurobehavioural disability (NBD) comprises elements of executive and attentional dysfunction, poor insight, problems of awareness and social judgement, labile mood, altered emotional expression, and poor impulse control, any or all of which can have a serious impact upon a person’s decision-making and capacity for social independence. The aim of this narrative review is to explore some of the more intrusive forms of NBD that act as obstacles to psychosocial outcome to act as a frame of reference for developing effective rehabilitation interventions. Special consideration is given to the psychosocial impact of three core forms of NBD: a failure of social cognition, aggressive behaviour, and problems of drive/motivation. Consideration is also given to the developmental implications of sustaining a brain injury in childhood or adolescence, including its impact on maturational and social development and subsequent effects on long-term psychosocial behaviour.